From «Hospital Mias» to «Hospital Infection» - S. A. Svistunov; I. A. Svistunova; A. A. Kuzin; D. A. Zharkov (Эпидемиология и вакцинопрофилактика)
The health of servicemen has always been one of the main factors playing a decisive role in the battle. The level of development of medical knowledge of military doctors plays an enormous role in maintaining the health of the personnel of the troops, together with their proper improvement. Sanitary losses of troops during the wars of the XIX-XX centuries have always been huge and depended mainly on infections, including wound infections, which many times exceeded the number of deaths during battles. Infectious complications of wounds of different genesis remain one of the most difficult problems of surgery in both peaceful and wartime. It should be noted, that Louis Pasteur was the first who spoke about infectious diseases at infectious diseases in 1862, and already in 1865, on the basis of Pasteur's experiments, the English surgeon Joseph Lister suggested using carbolic acid to fight infected wounds. These works laid the foundation of antiseptics, contributing to significant success in surgery. At the present time, new microorganisms have come to replace the classical pathogens of infectious diseases, contributing to the development of infectious complications, an increase in the duration of treatment and lethality.